Linking Participative Management with the Commitment of Employees in the Public Service Sector of a Nascent Economy - Monyei, Francis E.; Ukandu, Nnenna E.; Ukpere, Wilfred Isioma (Journal of Economic Development, Environment and People, 2026)
Employee commitment is a key factor influencing organizational performance, affecting productivity, job satisfaction, and staff retention. In today’s complex organizational environment, management approaches that actively involve employees in decision-making have become increasingly important. This study examined the impact of participative management, with particular emphasis on the open-door policy, on employee commitment and job satisfaction within public sector organizations. Using structured questionnaires, data was gathered from 251 employees in a few chosen offices as part of a descriptive survey research methodology. Simple linear regression, percentages, and frequency distributions were used to analyse the data. Employee commitment and job satisfaction are positively impacted by participative management methods, particularly open-door policies, according to the data. Employees who perceive management as approachable and inclusive demonstrate higher levels of motivation, loyalty, and satisfaction with their work. As per the study's findings, encouraging participative management is a successful strategy for raising employee loyalty and improving overall organisational effectiveness. Based on these results, it is advised that in order to sustain high levels of employee commitment and happiness, organisations set up organised methods for employee engagement, guarantee leadership accessibility, and promote active involvement in decision-making.